Alveolate porous carbon aerogels supported Co9S8 derived from a novel hybrid hydrogel for bifunctional oxygen electrocatalysis - Hu, Xuejiao (2021)
Incorporation of transition-metal dopants into carbon aerogels is a powerful way to develop highly-active and robust bifunctional oxygen electrocatalysts. Herein, we develop a novel hybrid hydrogel method for the preparation of Co9S8-doped alveolate carbon aerogels. The hydrogel formation depends on a simple sol−gel polymerization of chitosan, sodium tripolyphosphate and polyhexamethyleneguanidine phosphate. The repeating units of polymer contain a binding site (single bondNH2) for Co2+ ions, after pyrolysis which ensures a uniform anchor of Co9S8 particles within the carbon aerogels. The newly developed catalyst exhibits excellent bifunctional activity and robust stability for both the oxygen reduction reaction and oxygen evolution reaction, resulting from the significant synergy between Co9S8 and 3D porous N, P-codoped carbon aerogels. Moreover, we also demonstrate that Co9S8 material is more active to OER than to ORR through the density functional theory (DFT) theoretical computation.